Implementasi Layanan Hotline Dan Aplikasi Emergency Button PSC 119 Guna Meningkatkan Akses Dan Mutu Penanganan Kegawatdaruratan Di Kabupaten Tulungagung - Salsa Bella, Vivtania; Endang Indartuti; Dida Rahmadanik (Faculty of Social and Political Science, 2024)
Emergency situations are conditions that need attention wherever and whenever they occur. The government has issued regulations regarding the Integrated Emergency Response System (SPGDT), but its implementation is not yet uniform. During emergencies, both medical and non-medical services needed by patients must be provided promptly. The Public Safety Center is a service for emergency cases conducted swiftly, accurately, and carefully for the community. Several regions that have implemented this service continue to develop the services provided to have a greater impact, one of which is the Public Safety Center of Tulungagung Regency, which currently implements the hotline service and the Emergency Button Public Safety Center 119 application, and from the developed services, numerous achievements have been obtained. Apart from the achievements of the developed services, the Public Safety Center of Tulungagung Regency is the first of its kind in Indonesia, thus attracting attention to see in detail how the implementation process of these services is carried out. The implementation analysis conducted in this research is based on Merilee S. Grindle's implementation theory, which consists of two major variables: content of policy and context of implementation, using qualitative research methods. The results show that the implementation process is indeed structured and clear or detailed in each of its indicators, but reinforcement is still needed in several indicators to maximize the implementation process.